The influence of microbiota on the development and course of inflammatory diseases of periodontal tissues - Demkovych, Andrii; Kalashnikov, Dmytro; Hasiuk, Petro; Zubchenko, Sergiy; Vorobets, Anna (Frontiers in Oral Health, 2023)
An important feature of the functioning of the organs and tissues of the oral cavity is the fact that all processes that take place in it are carried out in the constant presence of various microorganisms that cause the development of pathological processes in the body or are associated with them. In the pathogenesis of chronic generalized periodontitis, dental plaque penetrates the bottom of the gingival sulcus, penetrating under the epithelium into the stroma of the connective tissue, causing its inflammation. Bacteria produce a number of toxic substances that have a toxic effect on surrounding tissues. Most bacteria produce chain fatty acids that inhibit chemotaxis of leukocytes and phagocytes. Anaerobes and spirochetes secrete a number of substances (propionic acid and indole) that are extremely toxic to most tissues. Inflammation in the periodontal tissues is caused by the microbiota of the dental plaque biofilm. As periodontitis develops, an increase in the number of P. gingivalis, P. intermedia and T. forsythia was found in it, more than 100 times.Therefore, the given data prove that in the development and course of the inflammatory process in the periodontal tissues, complex dysbiotic and tissue-cellular interactions are involved, the dynamic balance of which depends on its outcome.